Unlocking Arabic Texts: How Nahwu Proficiency Shapes Students’ Qirā’ah Skills at a Pesantren - Simamora, Risky Samina; Yunaldi, Yunaldi (al-Ittijah: Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2025)
Nahwu (Arabic grammar) is a foundational component of the Islamic boarding school curriculum, serving as a critical framework for structural linguistic analysis and the development of reading proficiency (mahārah al-qirāʾah). This study investigates the correlation between grammatical comprehension and reading ability at the Pondok Pesantren Salafiyah Islamiyah (Islamic Boarding School) in Padang Bujur. Employing a quantitative correlational design, the research sampled eighth-grade students using grammar tests and performance-based assessments of turāts books. Data were analyzed via the Pearson Product-Moment correlation test. he findings demonstrate a significant positive correlation (0.845 > 0.444), leading to the rejection of the null hypothesis (H₀). These results conclude that robust mastery of nahwu is a significant predictor of a student's ability to decipher classical Arabic texts. Theoretically, this reinforces the need for integrated instruction that balances grammar with textual application. Practically, it suggests that strengthening grammatical foundations is essential for classical literacy. However, this study is limited by its single-institution focus and narrow demographic, which may affect generalizability. Future research should expand the sample size across multiple institutions and employ mixed-methods approaches to explore how diverse instructional strategies and qualitative factors, such as student motivation, influence the synergy between grammatical mastery and reading proficiency.